DEKRADASI PERDA KOTA SERANG NOMOR 1 TAHUN 2011 DAN IMPLEMENTASINYA DI KOTA SERANG - Dian Pertiwi (JURIS (Jurnal Ilmiah Syariah), 2019)
One of the proposed local government regulations (Perda) proposed by the members of district parliament  (DPRD) of the city of Serang is Perda number 1 year 2011 about the annual parking system in the side of  public road which received records from the Ministry of Home Affairs and Ministry of Finance so that it could not be implemented in Serang City.  The focus of this research is the implications of the unenactment of Perda number 1 year 2011 against the implementation of the local government of Serang. The research method used was qualitative with normative and juridical approach empirically. The results showed that Perda of Serang City initiative could not be enforced because it is contrary to the higher Perda.  Its implications for the regional government of Serang City is the parliament of Serang was not working well in impelementing their legislation function.